• anonymous
For the polynomial 6xy2 – 5x2y? + 9x2 to be a trinomial with a degree of 3 after it has been fully simplified, the missing exponent of the y-term must be ?
  • Stacey Warren - Expert
Hey! We 've verified this expert answer for you, click below to unlock the details :)
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
  • katieb
I got my questions answered at in under 10 minutes. Go to now for free help!
  • anonymous
Example 1. Factor 30. Solution. 30 = 2· 15 = 2· 3· 5 If we begin 30 = 5· 6, we still obtain -- apart from the order -- 5· 2· 3. Problem 1. Factor 50. To see the answer, pass your mouse over the colored area. To cover the answer again, click "Refresh" ("Reload"). Do the problem yourself first! 50 = 2· 25 = 2· 5· 5 Factoring, then, is the reverse of multiplying. When we multiply, we write 2(a + b) = 2a + 2b. But if we switch sides and write 2a + 2b = 2(a + b), then we have factored 2a + 2b as the product 2(a + b). In this sum 2a + 2b, 2 is a common factor of each term. It is a factor of 2a, and it is a factor of 2b. This Lesson is concerned exclusively with recognizing common factors. Problem 2. Factor 3x − 3y. 3x − 3y = 3(x − y) Problem 3. Rewrite each of the following as the product of 2x and another factor. For example, 10x3 = 2x· 5x2. Rule 1 of exponents. a) 8x = 2x· 4 b) 6ax = 2x· 3a c) 2x2 = 2x· x d) 2x3 = 2x· x2 e) 4x10 = 2x· 2x9 f) 6x5 = 2x· 3x4 g) 2ax6 = 2x· ax5 h) 2x = 2x· 1

Looking for something else?

Not the answer you are looking for? Search for more explanations.